Factors for the Digitalisation of Political Parties in Portugal and Spain: A Comparative Perspective - González-Cacheda, Bruno; Cancela Outeda, Celso; Cordal, Constantino (PARTECIPAZIONE E CONFLITTO, 2022)
This investigation stems from the need to better comprehend the digitalisation of the Iberian parties and, especially, to understand the lack of scientific knowledge surrounding the digitalisation of political actors in Portugal. The principal objective of this investigation is the betterment of knowledge of the factors that intervene in the digitalisation of political parties. Taking various theoretical premises into account, we will analyse the relation between the age of the parties, the ideology and the stability of the party system, and the adoption of digital instruments for the purposes of contact, participation, deliberation, and mobilisation of financial resources between political parties with parliamentary representation in Portugal and Spain. To answer these questions the investigation used a data matrix taken from six qualitative variables applied to each of the analysed political parties. The results show a tendency towards a greater level of digitalisation in political parties located on the left of the ideological spectrum that were founded after the year 2008. Furthermore, the stability of the party system and a lower competitive capacity could partially explain the lower level of digitalisation in political parties in Portugal.